De la metáfora náhuatl: la construcción de la divinidad en dos textos sahaguntinos - C. Zinni, Mariana (El Colegio de México, 2013)
I would like to analyze the concept dios/teútl in two Sahaguntian textsas a metaphoric construction, in order to bring to light certain doctrinalunderstanding between two completely different hermeneutical worlds: the Christian and the Nahua. The main objective of suchmetaphorical device would be to undertake a more efficient evangelizationand to promote the “conquest” and new order of foreign cognitiveschemes. By settling unprecedented metaphors, it will be possible,for instance, to promote the appearance of an open and dangeroussemantic space to pre-decir, or to say something new, for the very firsttime in a situation of evangelization. I propose the study of these newmetaphors as a form of “adjusted mimesis” that will allow us to revisefriar Sahagún’s intervention, aimed towards a deeper degree of communication.